Pilot selection : psychological principles and practice - Bor, Robert; Eriksen, Carina; Hubbard, Todd; King, Raymond E., 1959- (New York, NY : CRC Press, Taylor & Francis Group, 2019)
"This comprehensive book describes in practical and ethical terms how recruitment, selection, and psychological assessment can be conducted amongst pilots. It includes chapters written by experts in the field on domains and related areas, such as air traffic controllers and cabin crew. The book is written for airlines, senior pilots responsible for recruitment and training, human resources specialists, human factors and safety specialists, occupational health doctors, psychologists, AMEs, practitioners or academics involved in pilot selection"--
Part 1: History and Rationale for Pilot Selection 1. History of pilot selection 2. Rationale for pilot selection 3. Selecting the selectors 4. Job plans and job analysis 5. Psychometric testing: test construction, validation and norms 6. Ethics in psychometric testing 7. Tests commonly used in pilot selection Part 2: The Pilot Selection Process 8. The recruitment process 9. Selecting for high risk roles 10. Selecting for initial trainee -- V -- licensed crew 11. Interviewing skills for pilot selection 12. The simulator and its use in pilot selection 13. Giving feedback to applicants Part 3: Assessment with Selection of Pilots 14. Mental health assessment 15. Personality assessment 16. Personality disorder and its clinical assessment in aviation 17. Personality and training 18. Neurocognitive assessment 19. Medical assessment 20. Assessing 'fit' with the company and organisation 21. Assessment report preparation 22. Training of Aviation Psychologists Part 4: Pilot Careers 23. Ability, aptitude and performance assessment 24. Pilot work appraisals and career coaching 25. Selection for command 26. Preparing pilots for retirement Part 5: Other Aviation Selections 27. Selection of remote pilot/UAV operators 28. Selection in military settings 29. Selection of helicopter pilots 30. Selection of 'bush pilots' 31. Selection in air traffic control 32. Selection of cabin crew 33. Selection of maintenance engineers 34. Astronaut selection 35. The pilotless aircraft 36. Aviation psychologist careers and selection
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: Air pilots -- Selection and appointment; Aviation psychology; TRANSPORTATION / Aviation / Piloting & Flight Instruction; TRANSPORTATION / Aviation / Commercial